The role of team leadership on Search and Rescue (SAR) team performance in disaster management / Norsyazwani Ab Halim, Azlyn Ahmad Zawawi, and Ashrul Riezal Asbar - Ab Halim, Norsyazwani; Ahmad Zawawi, Azlyn; Asbar, Ashrul Riezal (Universiti Teknologi MARA, Kedah, 2023)
Disaster management in Malaysia was ingrained to manage calamity depending on the degree of a disaster before, during, and after disasters occur. The Search and Rescue (SAR) team refers to individuals with the necessary experience and intelligence to search for people in distressed circumstances such as victims of natural phenomena, trapped at the top, or lost in deserts. Based on this notion, this study aimed to examine the direct relationship between team leadership and aid team performance and the indirect relationship between team leadership and rescue team via the mediating role of team motivation. A total of 100 SAR team members from nine states in Peninsular Malaysia participated in this study. Data were collected using questionnaires distributed to the SAR team of the Fire and Rescue Department of Malaysia (FRDM). The Partial Least Squares (PLS) Version 3 and Statistical Package for the Social Sciences (SPSS) Version 26 analyzed the hypotheses. The results indicated a significant positive relationship between team leadership and team performance and a significant relationship between team leadership and team performance via the mediating role of team motivation.